Genetically Modified Food - Keith R. Schneider; Renée Goodrich Schneider; Susanna Richardson (EDIS)
A food is considered genetically modified when its genetic makeup is altered in some way as a result of the use of recombinant DNA biotechnological procedures. These changes result in the expression of attributes not found in the original. Examples include delayed-ripening tomatoes and pest-resistant or herbicide-tolerant crops. Genetic modification can be used to improve crop yields, reduce insecticide use, or increase the nutritional value of foods. This revised 5-page fact sheet answers questions consumers might have about genetically modified food. Written by Keith R. Schneider, Renée Goodrich Schneider, and Susanna Richardson, and published by the UF Department of Food Science and Human Nutrition, November 2014. (Photo: iStock/Thinkstock.com)